2014
DOI: 10.1007/s11899-014-0228-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of MPN: What Do We Know?

Abstract: The myeloproliferative neoplasms, are characterised by overproduction of myeloid cells. Chronic myeloid leukaemia, polycythaemia vera, essential thrombocythaemia, myelofibrosis and the very rare disorders chronic neutrophilic leukaemia, chronic eosinophilic leukaemia not otherwise specified and mastocytosis are all included in the group. Incidence and prevalence rates reported in the worldwide literature are presented in this review. Survival data on each condition is described. Information on the aetiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 93 publications
(107 reference statements)
0
27
0
2
Order By: Relevance
“…In this large population-based study on incidence of MPNs in Sweden during recent years, we found the age-adjusted incidence for all MPNs to be 4.45 (4.34-4.56)/100 000 person-years which is in the higher range of what has been previously reported in Western countries. [10,11,16] There was an increase in age-standardized MPN incidence rates during the study period which most likely reflects earlier detections of MPN cases through more widespread screening as well as improved reporting to the cancer register. [31] The strong association between higher age and high incidence of MPNs underlines that MPNs are primarily diseases of the older population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this large population-based study on incidence of MPNs in Sweden during recent years, we found the age-adjusted incidence for all MPNs to be 4.45 (4.34-4.56)/100 000 person-years which is in the higher range of what has been previously reported in Western countries. [10,11,16] There was an increase in age-standardized MPN incidence rates during the study period which most likely reflects earlier detections of MPN cases through more widespread screening as well as improved reporting to the cancer register. [31] The strong association between higher age and high incidence of MPNs underlines that MPNs are primarily diseases of the older population.…”
Section: Discussionmentioning
confidence: 94%
“…[8,9] The incidence rates of MPNs vary substantially between different reports, ranging from 1.15 to 4.99/100 000 person-years for all subtypes of MPNs combined. [10][11][12][13][14][15][16][17][18][19] The majority of published studies originate from Europe, North America, and Asia and large variations are noted between different countries, cancer registers and calendar periods. The highest incidences are observed in regional studies performed prior to the year 2000, while lower figures have been observed in larger register-based studies.…”
Section: Introductionmentioning
confidence: 99%
“…Transitional stages are common , and the final stages of these neoplasms are characterised by bone marrow failure, myelofibrosis and leukaemic transformation . A biological continuum has been proposed to exist, implying clonal evolution from early cancer stage (ET, PV) to the advanced cancer stage – myelofibrosis .…”
mentioning
confidence: 99%
“…Other than these mutations, the aetiology of the MPNs is mostly unknown . However, chronic inflammation has recently been proposed as a trigger and driver of clonal evolution in MPNs .…”
mentioning
confidence: 99%
“…7 MF, both primary and secondary, is estimated to have a yearly incidence of one to 1.5 per 100,000 persons 8 . However, the true incidence is not known and may be higher than estimated due to underdiagnosis, and differences in reporting methods used 9–12 .…”
Section: Introductionmentioning
confidence: 99%